2011
DOI: 10.1108/17561371111131317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial liberalization on agricultural growth: a case study of Pakistan

Abstract: PurposeThe purpose of this paper is to develop a financial liberalization index (FLI) and evaluate its impact on agricultural growth.Design/methodology/approachThe study uses the autoregressive distributed lag approach to determine the long run and short coefficients.FindingsThe empirical results show that FLI affects agricultural growth positively in the short and the long run; but real interest rate positively affects agricultural growth in the short run and negatively in the long run.Originality/valueWhile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Anthony (2010) investigated the role of formal agriculture credit for Nigerian economy with exchange rate and interest rate and found that formal agriculture credit improve the agriculture performance and economic progression. Muhammad Adnan Hye and Wizarat (2011) analysis the financial liberation effect on agriculture found that financial liberation helps to agriculture growth in Pakistan and same outcomes observed by Shahbaz et al (2013) for same country.…”
Section: Review Of Literaturesupporting
confidence: 65%
“…Anthony (2010) investigated the role of formal agriculture credit for Nigerian economy with exchange rate and interest rate and found that formal agriculture credit improve the agriculture performance and economic progression. Muhammad Adnan Hye and Wizarat (2011) analysis the financial liberation effect on agriculture found that financial liberation helps to agriculture growth in Pakistan and same outcomes observed by Shahbaz et al (2013) for same country.…”
Section: Review Of Literaturesupporting
confidence: 65%
“…As the distance to the place of sale increases, the household faces a higher transport cost and maybe discouraged to sell his perishable agricultural produce at a larger distance. This would in turn drive the households towards diversification of their income portfolios [26][27][28][29][30]. Hence, over larger distances, the agricultural output, which is mostly perishable and can degrade over large distances, is not likely to be sold by the households.…”
Section: Results and Analysismentioning
confidence: 99%
“…Financial institutions will reduce financial support for agriculture under the effect of both economic profit and risk-taking. In contrast to the above view, as the gap between the return on investment in agriculture and the commercial and industrial sectors closes and the credit conditions in the agricultural sector are optimized, some academics think that the market-oriented reform of financial institutions at this point has contributed to the deepening of inclusive financial services (Muhammad Adnan and Wizarat, 2011;Onuka and Odinakachukwu, 2020). On the other hand, most of the literature on the impact of financial credit on total factor productivity in food has looked at the micro demand side of financial credit constraints and availability.…”
Section: Introductionmentioning
confidence: 91%